Stage collapse-surgical treatment of patients with bilateral destructive pulmonary tuberculosis - Korpusenko I.V. (Medičnì Perspektivi)
Experience of surgical treatment of 14 patients with bilateral destructive pulmonary tuberculosis by our established methods was generalized. The video-assisted minimally invasive thoracoplastics of 5 – 6 ribs was performed to all patients on the side of massive destruction (presence of large caverns, several caverns, focal dissemination). Second stage of collapse-surgical treatment was performed in 2 – 3 months. Method of extrapleural pneumolysis was used in patients with upper – posterior localization of cavities in the contralateral lung. Patients with inferior lobe localization of cavities in the contralateral lung were operated by the developed method of inferior lobe treatment. The video-assisted extrapleural technique was used in patients with bilateral destructive pulmonary tuberculosis because of impossibility to use resection intervention on the side of a massive destruction, it being surgical operation of choice due to a mild postoperative period course, early activation of patients, less pronounced pain syndrome.